Association analysis of EIF4G1 and Parkinson disease in Xinjiang Uygur and Han nationality. Issue 18 (May 2018) - Ma, Yu; Zheng, Daxiong; Li, Hongyan
Abstract : Abstract: This study is to investigate whether the known mutations P.R1205H and P.A502V were pathogenic factors of Parkinson disease (PD) in Xinjiang Uygur and Han people. A case–control study with polymerase chain reaction–restriction fragment length polymorphism method was performed on 150 cases of PD and 130 cases of age, sex, and national-matched healthy controls for rs200221361 polymorphism analysis and Sanger sequencing. Specific mutations were chosen for further sequencing in a case–control study. The 3 variants located on the exon 10, and the rs200221361 was a nonsynonymous variant. The frequencies of rs200221361 genotype and allele between PD and control groups in Uygur and Han people showed no significant difference (for genotype, χ 2  = 0.91, P  > .05; for allele, χ 2  = 0.91, P  > .05). Statistical analysis showed that there were no differences in allele and genotype frequencies of rs200221361 genotype and allele between PD and control groups among the age, gender, or race ( P  > .05). P.Ala502Val and P.Arg1205H may not be pathogenic mutations to PD in Xinjiang Uygur and Han people. The polymorphism of the rs200221361 may have no association with the occurrence of PD in Uygur and Han people of Xinjiang.